Hermeneutic’s Ibn Arabi: An Alternative in Understanding Texts for Islamic Moderation - Theguh Saumantri; Usman Ismail, Asep (UIN Sunan Kalijaga Yogyakarta, 2024)
The recent phenomenon of radicalism is attributed to rigid and intellectualistic interpretations of religious texts. Referring to the classical thought of Ibn Arabi, there is a common thread in understanding religious texts that involves not only a literal (dhahir) approach but also an inner (batin) approach. This inner approach creates a more inclusive and universal understanding of religious texts. The inner approach introduced by Ibn Arabi, known as ta’wil, is understood in philosophical studies as hermeneutics. Ibn ‘Arabi’s thought is particularly interesting for deeper examination because it introduces various essential themes in Sufism, such as Wahdat al-Wujud, the concept of prophethood, entities, and others. This is inseparable from his paradigm, rich in hermeneutics based on spiritual experience and distinctive mystical knowledge, setting him apart from other mystics. This study employs a literature review method with a hermeneutical approach to further explore Ibn Arabi’s hermeneutical concepts within the context of Islam. The findings indicate that the characteristics of Ibn Arabi’s knowledge paradigm can be observed through his hermeneutical methods, which are derived from the power of imagination, the use of symbols in understanding texts, and epistemology and sources of knowledge. These characteristics contribute to the development of epistemology in understanding religious texts, such as the Qur’an and Hadith.